ANALISIS PERPAJAKAN DAERAH DAN RETRIBUSI DAERAH DALAM MENINGKATKAN PENDAPATAN FISKAL OTONOMI DAERAH SIMALUNGUN - PIN PIN . (LP2MTBM MAKARIOZ, 2020)
The implementation of local government in accordance with the mandate of the Constitution of the Republic of Indonesia in1945, which regulates and manages government affairs according to the principle of autonomy and assistance duties, isdirected to accelerate the realization of community welfare through improvement, service, empowerment, and communityparticipation. As well as increasing regional competitiveness by paying attention to the principles of democracy, equality,justice, privileges and specificity of a region within the frame of the Unity Of the Republic of Indonesia (NKRI). Nationaldevelopment is an activity that takes place continuously and continuously aimed at improving the welfare of the people bothmateril and spritual. To be able to realize these goals, it is necessary to pay attention to the problem of developmentfinancing. One of the efforts to realize the independence of a nation or state in development financing is to explore thesource of funds derived from the community, namely taxes. Each autonomous region in this case provinces, regencies /cities in Indonesia, has natural resources and economic potentials that vary, so that if utilized optimally it will contributesignificantly to the acceptance of indigenous opinions of the region, which in turn will provide benefits for regionaldevelopment. Through various regional reception alternatives, The Law on Local Government and Financial Balancebetween central and local establish local taxes and levies as a source of Local Indigenous Income (PAD) sourced from thearea itself. PAD components that have excellent prospects for development is a local tax.